Impact and Challenges of Digital Marketing in Healthcare Industries during Digital Era and Covid-19 Pandemic - Khiong, Khie (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this study is to analyze the impact and challenges of digital marketing in health care industries during the digital era and covid-19 pandemic. The research method is a literature review. Search literature in this literature review using a database in the form of Google Scholar / Google Scholar, Biomed Central, NCBI , and Proquests. After the articles were collected, the researchers grouped a number of articles that had been obtained based on the relevance of digital marketing topics. The articles that are prioritized revolve around the last 5 years of research, but if there is knowledge or discussion that has not changed, it will be expanded to become articles with the last 10 years of research. Critical appraisal is a journal analysis process that is used as a theoretical basis regarding the differences, similarities and shortcomings of the journals used. Journals are reviewed to select journals of measurement results that are appropriate to the topic. From searches that have been done on Google schoolar from 2019 to 2022 that meet the research topic. The data used in this study is secondary data which means not from direct observation, but obtained from the results of research that has been carried out by previous researchers. Sources of secondary data obtained in the form of journal articles about research variables. The results of the analysis show that the impact of digital technology marketing has had a tremendous impact, namely increasing more engagement on social media and marketing, Key Performance indicators analyzing organizational values, growing demand for more digital, growing product searches among users, increasing demand for platforms Content, and this is demonstrated in many companies and organizations. During the COVID-19 pandemic, digital marketing has hit its growth charts and has made gains in technology around the world. Digital marketing in hospitals during this pandemic is a marketing strategy that has many benefits, namely it can attract new patients, expand business, increase customer/patient trust, strengthen customer/patient loyalty, increase brand awareness, encourage patients to use hospital services and promote it to other patients and family.